High electrocatalytic performance of N and O atomic co-functionalized carbon electrodes for vanadium redox flow battery. (January 2017) - Kim, Jiyeon; Lim, Hyebin; Jyoung, Jy-Young; Lee, Eun-Sook; Yi, Jung S.; Lee, Doohwan
Abstract: The effects of nitrogen and oxygen atomic co-functionalization of graphite felt (GF) by ammoxidation reactions for the positive and negative electrodes of vanadium redox flow battery (VRFB) are investigated. Ammoxidative surface reactions of the pristine-GF with NH3 /O2 results in effective N and O co-doping dominantly with kinetically relevant N and O functional groups; pyrrolic-N, pyridinic-N, and hydroxyl with high site densities. The intrinsic rate measurements reveal that the N and O co-functionalized GF electrodes (referred to as N-GF) afford one to several orders magnitude higher VO 2+ /VO2 + and V 2+ /V 3+ redox kinetics than the pristine-GF. Notably, the N and O co-functionalization gives rise to 2–3 folds greater reaction kinetics for both half-cell reactions than the conventional electrodes doped only with O functional groups (O-GF) at similar atomic contents. The high electrocatalytic properties of N-GF afford 4–6% greater voltage and energy efficiencies in VRFB than the conventional O-GF electrode at high current density (110 mA cm −2 ) with ∼38% higher initial charge-discharge capability owing to the significantly reduced overpotential. These results suggest the marked synergetic contributions of N and O co-functionalization of carbon electrode for facilitation of vanadium redox kinetics and the high effectiveness of the simple and scalable ammoxidation-based functionalization protocol. Graphical abstract: